2016
DOI: 10.1038/bmt.2016.182
|View full text |Cite
|
Sign up to set email alerts
|

Clinical separation of cGvHD and GvL and better GvHD-free/relapse-free survival (GRFS) after unrelated cord blood transplantation for AML

Abstract: Few studies have presented a comparison of myeloablative cord blood transplantation (CBT) and HLA-identical sibling hematopoietic cell transplantation (HCT) for AML in a disease-specific analysis, and the evaluation of GvHD-free and relapse-free survival (GRFS) in AML patients after unrelated CBT has not been reported. A total of 162 consecutive AML patients receiving intensified myeloablative unrelated CBT (n = 107) or allogeneic PBSC transplantation (allo-PBSCT) or bone marrow transplantation (BMT) from an H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
29
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 27 publications
0
29
1
Order By: Relevance
“…Despite the possible GVL effect, cGVHD was reported to have an adverse effect on NRM41 and was the main cause of poor quality of life after transplantation 42. However, low probability of cGVHD has always been one of the advantages of CB,43 and many studies reported that the relapse rate in CBT was similar to or lower than in other kinds of HCT,44, 45, 46 which reflected the clinical separation of cGVHD and the GVL effect in CB. Furthermore, our previous study showed that long‐term survivors with CBT had less cGVHD and higher quality of life compared to HCT in HLA‐identical sibling's donors 47.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the possible GVL effect, cGVHD was reported to have an adverse effect on NRM41 and was the main cause of poor quality of life after transplantation 42. However, low probability of cGVHD has always been one of the advantages of CB,43 and many studies reported that the relapse rate in CBT was similar to or lower than in other kinds of HCT,44, 45, 46 which reflected the clinical separation of cGVHD and the GVL effect in CB. Furthermore, our previous study showed that long‐term survivors with CBT had less cGVHD and higher quality of life compared to HCT in HLA‐identical sibling's donors 47.…”
Section: Discussionmentioning
confidence: 99%
“…Both HLA‐mismatched HSCT and DLI have a stronger antitumor effect than HLA‐matched HSCT, but they may also bring a greater risk of GVHD, one of the fatal complications after HSCT . Therefore, efforts have been made over the last 2 decades to explore the difference between the mechanism of GVT and GVHD and to design strategies to separate GVT from GVHD . One important difference is that the threshold number of T cells triggering GVT is relatively lower.…”
Section: Discussionmentioning
confidence: 88%
“…(31)(32)(33)(34) Therefore, efforts have been made over the last 2 decades to explore the difference between the mechanism of GVT and GVHD and to design strategies to separate GVT from GVHD. (35,36) One important difference is that the threshold number of T cells triggering GVT is relatively lower. This assumption is supported by clinical experience that low-dose DLI is generally sufficient to reduce the risk of relapse of the tumor without GVHD.…”
Section: Discussionmentioning
confidence: 99%
“…Those data clearly indicate that in patients with a similar bulk of disease at transplant, CBT would reduce relapse incidence and be preferable to other hematopoietic cell sources. More recently, an encouraging report from China showed that the relapse incidence was significantly lower after CBT than for BMT/PBSCT from matched sibling donors for AML [50], suggesting again that the GVL effects after CBT might be stronger than those after matched related BMT/PBSCT. Our study showed the relapse incidence at 2 years after CBT was 26% even in patients with nonremission myeloid malignancies, which was better than previous reports of allogeneic BMT/PBSCT for nonremission patients [41,51].…”
Section: Discussionmentioning
confidence: 99%